Pendapatan Keluarga dan Status Gizi Balita terhadap Kejadian Stunting - Devi Ayu Ari Meylanda; Desi Ernita Amru; Afif D Alba (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Stunting is a chronic nutritional problem that has a long-term impact on physical growth, cognitive development, and the quality of human resources in the future. This study aims to determine the relationship between family income and nutritional status of toddlers on the incidence of stunting in the Bukit Cening Daik Health Center working area, Lingga Regency, 2024. This study used a cross-sectional design with a sample size of 62 respondents selected through purposive sampling technique. Data were collected using questionnaires and anthropometric measurements, then analyzed using the chi-square test. The results of the analysis showed that there was a significant relationship between family income and nutritional status of children under five with the incidence of stunting (p < 0.05). This finding suggests that economic conditions and nutritional status play an important role in preventing stunting. Therefore, nutrition interventions targeting low-income families need to be strengthened to reduce stunting in the area.